2006
DOI: 10.1007/s10637-006-7589-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of the human biotransformation pathways of aplidine, a novel marine anti-cancer drug

Abstract: Aplidine is a potent marine anti-cancer drug and is currently being investigated in phase II clinical trials. However, the enzymes involved in the biotransformation of aplidine and thus its pharmacokinetics are not known yet. To assess the biotransformation pathways of aplidine and their potential implications for human pharmacology and toxicology, the in vitro metabolism of aplidine was characterized using incubations with human plasma, liver preparations, cytochrome P450 (CYP) and uridine diphosphoglucuronos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…The general methodology of synthesis consisted of: 1) incorporation of the first Fmoc-amino acid (Aaa1) onto a solid support, thereby forming an ester bond, 2) elongation of the peptide chain with three amino acids (Aaa2, Aaa3, Aaa4) using a Fmoc/tBu/Alloc strategy. Thus, Aaa3 was incorporated using Fmoc-AaaA C H T U N G T R E N N U N G (Alloc)-OH, 3) the Alloc group was removed with PdA C H T U N G T R E N N U N G (PPh 3 ) 4 in the presence of PhSiH 3 under an atmosphere of argon, 4) the elongation of the peptide sequence was continued through the free side chain with the following amino acids (Aaa5, Aaa6, Aaa7 (protected with acid labile protecting group), and Aaa8), 5) peptide cleavage and deprotection of the side chain; 6) peptide cyclizaton in solution, and finally 7) the purification and characterization of target product.…”
Section: Preparation Of Ib-01212 Analogues Using a Linear Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The general methodology of synthesis consisted of: 1) incorporation of the first Fmoc-amino acid (Aaa1) onto a solid support, thereby forming an ester bond, 2) elongation of the peptide chain with three amino acids (Aaa2, Aaa3, Aaa4) using a Fmoc/tBu/Alloc strategy. Thus, Aaa3 was incorporated using Fmoc-AaaA C H T U N G T R E N N U N G (Alloc)-OH, 3) the Alloc group was removed with PdA C H T U N G T R E N N U N G (PPh 3 ) 4 in the presence of PhSiH 3 under an atmosphere of argon, 4) the elongation of the peptide sequence was continued through the free side chain with the following amino acids (Aaa5, Aaa6, Aaa7 (protected with acid labile protecting group), and Aaa8), 5) peptide cleavage and deprotection of the side chain; 6) peptide cyclizaton in solution, and finally 7) the purification and characterization of target product.…”
Section: Preparation Of Ib-01212 Analogues Using a Linear Strategymentioning
confidence: 99%
“…The synthetic process was performed basically as described for Fragment A and the Alloc group was removed with a catalytic amount of PdA C H T U N G T R E N N U N G (PPh 3 ) 4 in the presence of PhSiH 3 under an atmosphere of argon. Later the Fmoc-Aaa5-OH was introduced through the side chain of Aaa3 using DIPCDI and HOAt methods.…”
Section: Preparation Of Ib-01212 Analogues Using a Linear Strategymentioning
confidence: 99%
“…Another possible mechanism involves the oxidative metabolite to form aldehyde metabolites and an olefin metabolite followed by P450-mediated deformylation (Prakash et al, 2008). Aplidine, a potent marine-derived anticancer drug, is C-demethylated at the (R)-N-methylleucine group by CYP2A6 in pooled HLMs (Brandon et al, 2007). In the present study, P450 enzyme reaction phenotyping strongly suggested that KRO-105714 is primarily metabolized by monohydroxylation and C-demethylation at the alkoxy group moiety by CYP3A4 in HLMs.…”
Section: Discussionmentioning
confidence: 51%
“…by mass spectrometry) was not feasible. Earlier in vitro studies have shown that human metabolism of trabectedin is mediated by CYP450 enzymes with a major role for 3A4 and minor contributions of 2C9, 2C19, 2D6, and 2E1 [13,17]. The expression of CYP450 enzymes (including CYP3A2, the rodent counterpart of human CYP3A4) in rats and mice is known to be sexdependent [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of metabolites from biological matrices and further structural elucidation is very difficult because of their very low concentrations [15]. Metabolic and degradation products were identified after incubation with human serum, liver microsomes, and UDP-glucuronyl transferase [14], and in vitro studies with liver microsomes suggest that trabectedin is mainly metabolized by CYP3A4 and to a minor extent by CYPs 2C9, 2C19, 2D6 and 2E1 [13,17].…”
Section: Introductionmentioning
confidence: 99%